Temu Kembali Informasi pada Berita Olahraga Berbahasa Indonesia dengan Seleksi Fitur Term Frequency dan Metode BM25 - Rachmad Ridlo Baihaqi; Indriati Indriati; Sutrisno Sutrisno (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Coinciding with the progress of globalization in the modern era now, resulting in increased use of the World Wide Web (WWW) and the internet for sources that provide information online from various countries. A search engine is needed by internet users to search for information. Therefore, resulting in the number of documents stored in digital soared. The vast reach of readers and the short time resulted in the emergence of online media in broadcasting news. The information retrieval system is the function of obtaining information desired by the user or relevant through a query that has been filled out by the user. It is expected that the implementation of Information retrieval can be used in obtaining documents in accordance with user requirements. BM25 method is to calculate the value of similarity (similarity) and then do the ranking process of the similarity of the results of the query. Added to the term frequency feature selection when training data. The test is based on the precision @k value and the kappa measure value of 10 queries. The best value obtained on the precision @k test is when k = 5, with values ​​of 90% and 86%. For the value obtained from the kappa mesure test of 0.85.